The reporting of adverse events in Johannesburg academic emergency departments - Zoghby, Matthew Gabriel (My University, 2019)
Background. Adverse events (AE) are a common occurrence in healthcare systems; however, the frequency of AEs occurring in South Africa and especially Emergency Departments (ED) is unknown. Objectives. To describe the frequency of AEs experienced by Healthcare providers (HCP) and the frequency of formal reporting thereafter over a 12-month period. Methods. A cross sectional descriptive study was performed amongst HCPs at Helen Joseph Hospital and Chris Hani Baragwaneth Academic Hospital EDs. One hundred completed questionnaires were received. Whilst the primary outcome was the number of AEs experienced and reported over a 12-month period, other outcomes included perceived barriers to AE reporting. Results. One hundred questionnaires were analysed including 51 doctors and 49 nurses. All HCPs experienced at least 10 AEs over 1 year but only enrolled nurses (60%) and professional nurses (35%) reported at least 10 AEs. Nurses were 21 times more likely to report at least 10 AEs (p < 0.0001). Twenty four percent of AEs were deemed minor. Barriers to AEs were assessed with ‘no feedback was given’, ‘lack of time’ and ‘being unaware of the reporting processes’ being the most common. Conclusion. There are low levels of formal AE reporting, especially amongst doctors, within Johannesburg Academic EM Departments despite large numbers of AEs experienced. There are multiple barriers, which influence these reporting practices. Improved reporting systems are needed to affect a change in the current environment.
A dissertation submitted to the Faculty of Health Science, University of the Witwatersrand, in fulfillment of the requirements for the degree of Master of Medicine (Emergency Medicine). Johannesburg February 2019